Enhanced optical properties of Cu2O anchored on reduced graphene oxide (rGO) sheets. (27th July 2018) - Bhargava, Richa; Khan, Shakeel
Abstract: In this report, Cu2 O and Cu2 O/rGO nanocomposites were successfully synthesized through chemical reduction method using glucose as a reducing agent for GO. The x-ray diffraction and field emission scanning electron microscope was used to investigate the phase composition and microstructure of the as-prepared materials. The presence of different functional groups in the as-synthesized sample was analyzed by Fourier transform infrared spectroscopy. Raman spectroscopy was used to confirm structural aspects such as defects of synthesized Cu2 O/rGO nanocomposites. The optical properties of the as-prepared samples were analyzed by UV–vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. Urbach energy is calculated in order to find out the defects in the nanocomposites. Zeta potential analysis was done to study the surface charge and stability of the as-synthesized samples. These results show that the content of rGO introduced into nanocomposite improves the optical properties of Cu2 O thereby enhancing the utilization of visible light.